Isolation and detection of antibiotics resistance genes of Escherichia coli from broiler farms in Sukabumi, Indonesia - Hardiati, Aprilia; Safika, Safika; Wibawan, I Wayan Teguh; Indrawati, Agustin; Pasaribu, Fachriyan Hasmi (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This study aimed to isolate and identify Escherichia coli from broiler samples from Sukabumi, Indonesia. Also, antibiogram studies of the isolated bacteria were carried out considering the detection of the antibiotic resistance genes. Materials and Methods: Cloaca swabs (n = 45) were collected from broilers in Sukabumi, Indonesia. Isolation and identification of E. coli were carried out according to standard bacteriological techniques and biochemical tests, followed by confirmation of the polymerase chain reaction targeting the uspA gene. Antibiotic sensitivity test, using several antibiotics [tetracycline (TE), oxytetracycline (OT), ampicillin (AMP), gentamicin (CN), nalidixic acid (NA), ciprofloxacin (CIP), enrofloxacin (ENR), chloramphenicol, and erythromycin] was carried out following the Kirby– Bauer disk diffusion method. Detection of antibiotic resistance coding genes was carried out by PCR using specific oligonucleotide primers. Statistical analysis was carried out with one-way analysis of variance. Results: The results showed that 55.6% (25/45) of the samples were associated with the presence of E. coli. Antibiotic sensitivity test showed that the E. coli isolates were resistant to TE (88%; 22/25), OT (88%; 22/25), AMP (100%; 25/25), CN (64%; 16/25), NA (100%; 22/25), CIP (88%; 22/25), ENR (72%; 18/25), chloramphenicol (0%; 0/25), and erythromycin (92%; 23/25). On the other hand, the antibiotic resistance coding genes were tetA (86.4%; 19/22), blaTEM (100%; 25/25), aac(3)-IV (0%; 0/16), gyrA (100%; 25/25), and ermB (13%; 3/23). It was found that chloramphenicol is markedly different from other antibiotic treatment groups. Conclusion: Escherichia coli was successfully isolated from cloacal swabs of broiler in Sukabumi, Indonesia. The bacteria were resistant to TE, OT, AMP, CN, NA, CIP, ENR, and erythromycin. Chloramphenicol was more sensitive and effective than other antibiotics in inhibiting the growth of E. coli. The antibiotic resistance genes detected were tetA, blaTEM, gyrA, and ermB. J. Adv. Vet. Anim. Res., 8(1): 84-90, Mar 2021 http://doi.org/10.5455/javar.2021.h489